New Smart Power Management Hybrid System Photovoltaic-Fuel Cell - Benmessaoud, M.T. (Springer Verlag, 2019)
Currently, energy consumption in the planet is high, public awareness of energy consumption, environmental protection and steady progress in the deregulation of conventional energy, distributed generation systems (based on hydrogen) have attracted increased interest. Fuel cell (FC) base and high-temperature systems also have great potential in future single-source or multi-source (hybrid- HSE) applications due to their rapid technological development and numerous benefits such as well, as the appreciable efficiency, low emission (greenhouse gases) and flexible modular technology. Dynamic models for the main components of the system, namely the photovoltaic (PV) energy conversion system, fuel cells, electrolysers, electric power interconnection circuits, protective battery, storage tank of hydrogen, the gas compressors are developed. Two renewable energy modes, a photovoltaic field and a solid oxide fuel cell (SOFC) or Dynamics of proton exchange membrane fuel cells (PEMFC) with hydrogen storage system for generating part of system electrical energy is presented. Feasibility of using fuel cell (FC) for this system is evaluated by means of simulations. The electrical dynamic model, temperature change and dual layer capacity effect are considered in all simulations. Photovoltaic system (PV) output current is connected to the bus. Using a MPPT (maximum power point tracker) which is an electronic DC to DC converter that optimizes the match between the solar array and utility grid. The proposed system utilizes an electrolyser (EL) to generate hydrogen and a tank for storage. Therefore, there is no need for batteries. Moreover, the generated oxygen could be used in FCâs system and other applications. Moreover, such as the photovoltaic system, it is possible to connect fuel cell (FC) output voltage to DC bus alternatively. A controller model is presented to control flow of energy of system, hydrogen and oxygen to FC and improve transient and steady state responses of the output voltage to load disturbances. Simulations are carried out via MATLAB/SIMULINK and results show that the load tracking and output voltage are acceptable. Â© 2019, Springer Nature Switzerland AG.